ANALYSIS STUDY OF THE DYNAMICS OF THE PROCESS OF YARN TWISTING IN PNEUMO-MECHANICAL SPINNING - Ergashev , Zoirbek Nurmatjon ugli; Sayidmurodov , Mirzokhid Mirzarakhimovich (Educational Research in Universal Sciences, 2024)
The paper presents the results of a study of the dynamics of the process of torsion of yarn of pneumo-mechanical spinning in the presence of a stationary false twist reel, dynamic mathematical models of the process of twisting of yarn of pneumo-mechanical spinning in the presence of a stationary false twist reel, in unsteady modes of starting and stopping the forming-twisting device are constructed.